Prevention of Premature Ovarian Failure (POF) With Red Bean Supplementation: Case Study of Patients with Systemic Lupus Erythematosus - Muhammad Nooryanto, Kusworini Handono, Hani Susianti, I Wayan Arsana Wiyasa, Ettie Rukmigarsari (South Eastern European Journal of Public Health, 2025)
Introduction: Premature ovarian failure (POF) in women with SLE is a complex condition with serious health consequences, including psychological distress, infertility, osteoporosis, autoimmune disorders, and an increased risk of death. Objectives: This study aims to prove that red bean extract causes a decrease in NFkB, the number of atretic follicles, and an increase in E2 levels affect POF indicators in SLE. Methods: The research was conducted in a proper experimental laboratory with a post-test-only controlled group design. The subjects were female Balb/c mice given peroral red bean extract at 50, 75, and 100 mg/KgBB doses. The data was analyzed using SPSS 16 for Windows. A comparative test was performed through ANOVA, and a post-hoc Tukey test was performed. Results: This study proved that red bean extract caused a decrease in NFkB, the number of atretic follicles, and an increase in E2 levels affected POF indicators in SLE. Conclusions: For clinicians and the public, red beans can prevent POF in SLE patients. Red beans can be used as a preventive effort and early treatment of POF, reducing the incidence of POF in people with SLE.